2022
DOI: 10.1007/s43994-022-00007-4
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization, surface morphology and microstructure of water soluble colloidal MnO2 nanoflakes

Abstract: In the present work, characterization of water soluble colloidal MnO2 nanoflakes which act as an oxidizing agent was carried out using UV–visible spectroscopy. Transmission electron microscopy microstructure of colloidal MnO2 nanoflakes confirms the shape and nature of these particles. Selected area electron diffraction ring indicated that colloidal nanoflakes were amorphous in nature. Surface morphology of synthesized colloidal MnO2 nanostructure was determined by field emission scanning electron microscopy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The MSn-MOF's strong sorption capacity for AMX suggests that the sorbent may hold promise for actual usage in the elimination of AMX from wastewater. 51,52…”
Section: Resultsmentioning
confidence: 99%
“…The MSn-MOF's strong sorption capacity for AMX suggests that the sorbent may hold promise for actual usage in the elimination of AMX from wastewater. 51,52…”
Section: Resultsmentioning
confidence: 99%
“…Carbon quantum dots (CQDs) are uorescent semiconductor nanoparticles that have recently been used in pharmaceutical and biomedical analysis by measuring the enhancement or quenching of the uorescent signal from the CQDs as a result of an interaction of the CQDs with the compound of interest. [45][46][47][48][49][50] Originally, CQDs were prepared from primary chemical precursors such as citric acid, polyethyleneimine, zinc oxide, phenolic resins, and ethylene glycol, which were incompatible with concepts of green analytical chemistry. [51][52][53][54] Therefore, scientists have recently focused on nding environmentally friendly precursors from nature as substitutes, such as biomass wastes and plant-derived pharmaceuticals, because they are environmentally friendly, widely available, biocompatible, and rich in low-cost renewable raw materials (rich in C, H, N, and O atoms) such as polysaccharides, proteins, nucleic acids, and phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…parameters have a very strongly affected on heat transferred due to its very closeness on wall and it must be neglected if they are far from the wall. The utility of nanoparticles in many other applied fields than fluid dynamics exist, for instance see the the work of Ramadan et al,, 27 (Iqubal, Characterization, surface morphology and microstructure of water-soluble colloidal MnO 2 nanoflakes, 28 (Iqubal, Review on kinetic studies of α-hydroxy acids (glycolic, mandelic, citric, tartaric, and malic) and some other organic compounds with watersoluble nanoparticles of colloidal MnO 2 in absence and presence of non-ionic surfactant (TX-100). 29,30 Sreedevi et al 31 revealed that when carbon nanotubes and silver nanoparticles combine and are taken as hybrid nanoparticles then water is viewed as base fluid.…”
Section: Introductionmentioning
confidence: 99%